2016
DOI: 10.1515/cclm-2015-1202
|View full text |Cite
|
Sign up to set email alerts
|

Iohexol clearance in unstable critically ill patients: a tool to assess glomerular filtration rate

Abstract: GFR may be estimated by plasma iohexol clearance in unstable critically ill patients. This method is reliable, correlates very well with urinary iohexol clearance and does not depend on input/output fluid balance and fluid infusion, as compared with serum creatinine concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…However, seven studies in critically ill adults (n = 18-66) investigated the performance of several eGFR equations. Similar to our results, multiple SCr-based eGFR equations displayed high biases and low accuracy (23-60%, dependent on equation used) when compared with mGFR values [11,13,28,[37][38][39][40].…”
Section: Interpretation Of Performance Of Egfr Methodssupporting
confidence: 88%
“…However, seven studies in critically ill adults (n = 18-66) investigated the performance of several eGFR equations. Similar to our results, multiple SCr-based eGFR equations displayed high biases and low accuracy (23-60%, dependent on equation used) when compared with mGFR values [11,13,28,[37][38][39][40].…”
Section: Interpretation Of Performance Of Egfr Methodssupporting
confidence: 88%
“…In our patients, iohexol clearance was measured using a 24‐hour sampling schedule, delivering the mean GFR over 24 hours, encompassing all GFR variations (whether physiological, pathological—in unstable patients—or therapeutic) during this period. Nevertheless, in a previous work, Salmon‐Gandonnière et al demonstrated that the plasma iohexol concentration decay was steady within 24 hours in most patients and the fluid infusion volume or the use of catecholamines did not influence the iohexol pharmacokinetic parameters 18 . They also compared iohexol clearance calculated over 24 hours and over 6 hours and found that the variability of iohexol clearance over 24 hours was moderate (from 5 to 55%), suggesting that aggressive therapeutic interventions in the early period of ICU hospitalisation were not accompanied by parallel and rapid fluctuations of GFR.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, in a previous work, Salmon-Gandonnière et al demonstrated that the plasma iohexol concentration decay was steady within 24 hours in most patients and the fluid infusion volume or the use of catecholamines did not influence the iohexol pharmacokinetic parameters. 18 They also compared iohexol clearance calculated over 24 hours and over 6 hours and found that the variability of iohexol clearance over 24 hours was moderate (from 5 to 55%), suggesting that aggressive therapeutic interventions in the early period of ICU hospitalisation were not accompanied by parallel and rapid fluctuations of GFR. As a comparison, the coefficient of variation of creatinine clearance in healthy individuals can be as high as 35-45%, due to variability in both creatinine production and creatinine excretion.…”
Section: T a B L E 1 Patient Characteristicsmentioning
confidence: 99%
“…Mostly they are still subclinical and cannot be identified through serum creatinine levels. Consequently, early identification of potential abnormalities of renal function in cardiac patients plays an important role in early targeted therapy and reducing the occurrence of postoperative AKI [ 11 ].…”
Section: Discussionmentioning
confidence: 99%